EMOTIONAL BURNOUT RESEARCH AND ITS FACTORS IN PROGRAMMERS - Alpatova, Oleksandra; Alpatov, Serhii (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article analyzes the concept of emotional burnout, approaches to its study; psychological features of programmers' activities are considered; the factors causing emotional burnout among software developers are characterized; such factors of emotional burnout as overstrain at work due to excessive workload, devaluation of the essence of work, which becomes uninteresting, and emotional instability were investigated. The purpose of the article is a theoretical analysis and empirical description of emotional burnout and its factors in IT specialists. Methods of analysis of systematization and generalization of theoretical material of modern scientific sources on the problem of emotional burnout in professional activity. The following methods were used in the empirical study: Burnout questionnaire by K. Maslach, Test of motivational structure by F. Herzberg, Methodology of multifactorial personality research by R. Cattell, Methodology "Index of organizational tension", Questionnaire of self-organization of activity by E. Mandrikova; methods of mathematical processing: descriptive statistics (arithmetic mean, percentages), Student's T-shaped test, Pearson's R-correlation test including regression analysis. The results. It has been established that the main factors of programmer burnout are overstrain at work due to excessive workload, devaluation of the essence of work, and emotional instability. Conclusions: The conducted empirical study of the psychological factors of emotional burnout among programmers made it possible to single out the main organizational, motivational and personal factors that influence the formation of the burnout syndrome and its individual symptoms. Among the methods of prevention and correction of emotional burnout, the implementation of a system of providing psychological assistance in the organization is considered the most effective; training employees in simple methods of relaxation, distraction, switching attention, autogenic training and meditation; development of employees' ability to optimally distribute the workload, take rest breaks and realize the limitations of their own resources. When conducting psychocorrection of symptoms of emotional burnout, the main focus should be on restoring the normal functioning of the emotional sphere of employees, normalizing interpersonal relationships and forming a positive attitude towards professional activity and towards oneself as a specialist.